Safety and Efficacy of Direct Angioplasty in Acute Basilar Artery Occlusion Due to Atherosclerosis - Ma, Gaoting; Sun, Xuan; Tong, Xu; Jia, Baixue; Huo, Xiaochuan; Luo, Gang; Wang, Bo; Deng, Yiming; Gao, Feng; Song, Ligang; Ma, Ning; Miao, Zhongrong; et al. (Frontiers in Neurology, 2021)
Background and Purpose Endovascular treatment (EVT) is one of the promising treatment options in patients with intracranial atherosclerotic disease (ICAD)-related basilar artery occlusion (BAO). Here, we compared the safety and efficacy of direct angioplasty (DA) with stent-retriever thrombectomy (SRT) with or without rescue treatment in ICAD-related BAO. Methods We retrospectively evaluated 187 patients who underwent EVT for BAO from January 2012 to July 2018. We identified patients who underwent EVT due to ICAD-related BAO. Patients who accepted SRT with or without rescue treatment were classified into SRT group. Patients treated with DA with or without stent placement were classified into a DA group. Clinical and laboratory findings and outcomes were compared between groups. Results A total of 108 patients were enrolled, among whom 77 underwent SRT and 31 underwent DA; 61 (79.2%) SRT group patients underwent angioplasty with or without stent placement. Compared with patients in the SRT group, those in the DA group experienced a significantly shorter procedure time (60 min (60-120 min) vs. 120 min (60-120 min); p = 0.038) as well as a lower number of device passes (2 passes (1-2 passes) vs. 3 passes (2-4 passes); p ＜ 0.001). No significant differences in balloon angioplasty (35.5% vs. 22.1%; p = 0.150), emergent stent placement (64.5% vs. 57.1%; p = 0.481), successful recanalization (93.5% vs 85.7%; p = 0.340), distal or new territory embolization (3.2% vs 9.1%, p = 0.314) and reocclusion (22.6% vs 9.1%; p = 0.109) among DA and SRT groups were found. Additionally, no differences in symptomatic intracranial hemorrhage incidence (adjusted odds ratio, 0.74; 95% confidence interval, 0.06-9.44; p = 0.815), functional independence (adjusted odds ratio, 1.44; 95% confidence interval, 0.50-4.16; p = 0.497) and mortality rate (adjusted odds ratio, 0.36; 95% confidence interval, 0.06-2.04; p = 0.247) were noted among groups. Conclusions In certain patients suffering ICAD-related BAO, DA may shorten procedure time and reduce required device passes compared to SRT. Here, DA was retrospectively found to be of similar safety and efficacy as SRT.